2018
DOI: 10.1063/1.5006515
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and hyperthermia properties of CoxFe3-xO4 nanoparticles synthesized via cation exchange

Abstract: We demonstrate magnetic and hyperthermia properties of CoxFe3-xO4 (x = 0, 0.1, 0.3 and 0.5) nanoparticles synthesized via a simple cation exchange reaction of ∼12 nm Fe3O4 nanoparticles. The substitution of Fe cations with Co2+ ions leads to enhanced magnetocrystalline anisotropy and coercivity of the pristine superparamagnetic Fe3O4 nanoparticles. Hyperthermia measurement shows that by controlling the Co content (x = 0 to 0.5) in CoxFe3-xO4 nanoparticles, their specific absorption rate (SAR) can be greatly im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Recent work has shown that because of the large magnetocrystalline anisotropy constant ( K = 2 × 10 5 J/m 3 ) of cobalt, it can be used to effectively tune the magnetic properties through the controlled doping of Co in Fe 3 O 4 , MnFe 2 O 4 and ZnFe 2 O 4 nanoparticles [97,98,99]. A systematic adjustment of Co stoichiometry in Co x Fe 3-x O 4 ( x = 0, 0.1, 0.3 and 0.5) NPs from 0 to 0.5 results in an increase in magnetic anisotropy and coercivity with maximum value reached x = 0.5 (see Figure 9C) [99,100]. The M S value of Fe 3 O 4 nanoparticles is 86 emu/g, and it is decreased to 82, 78 and 77 emu/g, respectively with the increase of Co 2+ ion concentration due to the smaller magnetic moment of Co 2+ (3 µ B ) as compared to Fe 2+ (4 µ B ) [91].…”
Section: Enhancing Inductive Heating By Engineering the Magnetic Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that because of the large magnetocrystalline anisotropy constant ( K = 2 × 10 5 J/m 3 ) of cobalt, it can be used to effectively tune the magnetic properties through the controlled doping of Co in Fe 3 O 4 , MnFe 2 O 4 and ZnFe 2 O 4 nanoparticles [97,98,99]. A systematic adjustment of Co stoichiometry in Co x Fe 3-x O 4 ( x = 0, 0.1, 0.3 and 0.5) NPs from 0 to 0.5 results in an increase in magnetic anisotropy and coercivity with maximum value reached x = 0.5 (see Figure 9C) [99,100]. The M S value of Fe 3 O 4 nanoparticles is 86 emu/g, and it is decreased to 82, 78 and 77 emu/g, respectively with the increase of Co 2+ ion concentration due to the smaller magnetic moment of Co 2+ (3 µ B ) as compared to Fe 2+ (4 µ B ) [91].…”
Section: Enhancing Inductive Heating By Engineering the Magnetic Nmentioning
confidence: 99%
“…( B ) Blocking temperature vs. NPs size plot indicates a linear relationship between blocking temperature and NPs size [92]. ( C ) Hysteresis curves of Co x Fe 3- x O 4 nanoparticles with x = 0, 0.1, 0.3 and 0.5 at 10 K [100]. ( D ) Dependences of M S on the Zn and Co substitution content ( x ) in Fe 3 O 4 nanoparticles [99,102].…”
Section: Figurementioning
confidence: 99%
“…The methods widely used for the synthesis of magnetic Co x Fe 3−x O 4 NPs are as follows: co-precipitation, hydrothermal, reverse micelle, sol-gel, etc [39,40]. By doping Co ions into Fe 3 O 4 powders, Mohapatra et al [41] synthesized Co x Fe 3−x O 4 (0 <× 0.5) NPs, and performed hyperthermia measurements by applying various alternating magnetic fields. In this regard, increasing the intensity of the magnetic field from 184 to 491 Oe resulted in an increase in SLP from 81 to 132 W g −1 and 220 to 534 W g −1 for ferrofluids (having a concentration of 2 mg ml −1 ) of Fe 3 O 4 and Co 0.5 Fe 2.5 O 4 NPs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…While widespread research has been performed in the field of magnetic hyperthermia for materials such as Fe 3 O 4 and some ferrites, less attention has been paid to FORC investigations and the effect of Co concentration on magnetic hyperthermia properties of Co x Fe 3−x O 4 compound. In other words, the limited literature in this area is mainly focused on the investigation of structural and absorption properties of ferrites [10,12,41,[43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Among ferrites, CoFe 2 O 4 NPs are of considerable interest because of their moderate saturation magnetization, good chemical stability and high intrinsic magnetocrystalline anisotropy at room temperature [10]. The anisotropy constant of CoFe 2 O 4 ( K = 2 × 10 5 J·m −3 ) is nearly one order of magnitude larger than that of Fe 3 O 4 [1113]. Fe 3 O 4 NPs have been studied extensively for bio-medical applications, such as drug delivery [14], magnetic resonance imaging (MRI) and especially magnetic hyperthermia therapy, which is one of the efficient and new approaches for cancer treatment [4,15].…”
Section: Introductionmentioning
confidence: 99%